Dynamic Electrosorption Analysis as an Effective Means to Characterise the Structure of Bulk Graphene Assemblies. Issue 9 (10th January 2013) - Zhu, Junwu; Cheng, Chi; Yang, Xiaowei; Wang, Yufei; Qiu, Ling; Li, Dan
Abstract Restacking of graphene sheets to a graphite‐like structure is a prevailing problem that is known to compromise the performance of individual graphene sheets in an assembled bulk form. To address this common problem efficiently and monitor the structure and quality of graphene products comprehensively, it is highly desirable to develop reliable metrology techniques for characterising graphene‐based materials on a bulk assembly level and in a quantitative manner. Here, by revisiting the physicochemical principle of electrosorption, we propose a simple electrochemical approach, namely dynamic electrosorption analysis (DEA), as an easily accessible and effective technique for evaluation of the self‐stacking behaviour of graphene. Taking multilayered chemically converted graphene films as a model, we demonstrate that the DEA technique can effectively reveal very subtle variation in accessible surface area and pore size of graphene assemblies in the liquid phase and thus can provide useful insights to the experimental design relating to restacking control. This work also reveals the huge effect some routine processing conditions, such as heat treatment and drying, can have on the structure and performance of graphene‐based bulk materials, providing useful guidance for future manufacturing of this class of materials.